Differential Triggering of the Phenylpropanoid Biosynthetic Pathway Key Genes Transcription upon Cold Stress and Viral Infection in Tomato Leaves - Polyxeni Pappi (MDPI AG, 2021)
Plants develop a plethora of defense strategies during their acclimation and interactions with various environmental stresses. Secondary metabolites play a pivotal role in the processes during stress acclimation, therefore deciphering their relevant responses exchange the interpretation of the underlying molecular mechanisms that may contribute to improved adaptability and efficacy. In the current study, tomato plants were exposed to short-term cold stress (5 °C for 16 h) or inoculated (20 d) with either Cucumber Mosaic Virus (CMV) or Potato Virus Y (PVY). Responses were recorded via the assessments of leaf total phenolic (TP) content, total flavonoid (TF) levels, and phenylalanine ammonia-lyase (PAL) enzyme activity. The transcription of the gene families regulating the core phenylpropanoid biosynthetic pathway (PBP) at an early (PAL, cinnamic acid 4-hydroxylase, 4-coumarate-CoA ligase) or late (chalcone synthase and flavonol synthase) stage was also evaluated. The results showed that cold stress stimulated an increase in TP and TF contents, while PAL enzyme activity was also elevated compared to viral infection. Besides genes transcription of the enzymes involved in the core PBP was mostly induced by cold stress, whereas transcription of the genes regulating flavonoid biosynthesis was mainly triggered by viral infection. In conclusion, abiotic and biotic stressors induced differential regulation of the core PBP and flavonoid biosynthetic metabolism. Taking the above into consideration, our results highlight the complexity of tomato responses to diverse stimuli allowing for better elucidation of stress tolerance mechanisms at this crop.